Understanding auditory processing disorders - Yalçinkaya, Fulya; Keith, Robert (The Turkish Journal of Pediatrics, 2008)
Auditory processing disorders (APD) are defined as difficulties in hearing and understanding speech in the presence of normal peripheral hearing. Children with APD appear to be uncertain about what they hear, and have difficulties listening in background noise, following oral instructions, and understanding rapid or degraded speech. Suspicious behaviors include: "not listening", "unable to follow direction", or "unable to learn from information they hear". These children are often inattentive. The diagnosis can be complicated because other types of childhood disorders may exhibit similar behaviors (e.g., attention deficit disorders [ADD]). Therefore, results of auditory processing tests are important to differentiate between APD and ADD. In the following report we will briefly review the nature of APD in order to raise clinical awareness of this disorder.